The Comparison of The Efficacy of Photobiomodulation and Ultrasound in the Treatment of Chronic Non-specific Neck Pain: A Randomized Single-Blind Controlled Trial - Kenareh, Raheleh; Mirmohammadi, Seyyed Jalil; Khatibi, Amidoddine; Shamsi, Farimah; Mehrparvar, Amir Houshang (Journal of Lasers in Medical Sciences, 2021)
Introduction: Chronic neck pain is a common complaint among office workers. The aim of the present study was to compare the efficacy of a high-intensity laser and physiotherapy in office workers who were diagnosed with chronic non-specific neck pain. Methods: This study was a single-blind randomized controlled trial, with parallel allocation. Sixty office workers with chronic neck pain, aged between 25 and 55 years, participated in the study. The participants were randomly divided into two groups: photobiomodulation (by a high-level laser) and physiotherapy. Visual analog scale (VAS), Neck Disability Index (NDI), Neck Pain and Disability Scale (NPDS), and Bournemouth Questionnaire (BQN) were completed on three occasions (before, immediately, and 2 weeks after the intervention) to assess and compare the efficacy of the high-intensity laser and physiotherapy in neck pain. Data were analyzed by SPSS 23 software using the chi-square test, Student’s t-test, multivariate tests, and Fisher’s exact test. Results: The mean age of the participants was 37.53±9.52 and 41.16±7.85 years in physiotherapy and laser therapy respectively. The VAS score and NDI scores decreased after both kinds of interventions, and the effect of photobiomodulation was significantly higher than physiotherapy (P<0.001). Both treatment modalities significantly affect different aspects of chronic neck pain assessed by NDPS and BQN questionnaires and the effect of photobiomodulation was more prominent than physiotherapy. Conclusion: The findings of this study showed that photobiomodulation and physiotherapy can reduce chronic neck pain and its different aspects and the effect of laser therapy was significantly higher than physiotherapy DOI: 10.34172/jlms.2021.20